Small Multitarget Molecules Incorporating the Enone Moiety - Thalia Liargkova; Nikolaos Eleftheriadis; Frank Dekker; Efstathia Voulgari; Constantinos Avgoustakis; Marina Sagnou; Barbara Mavroidi; Maria Pelecanou; Dimitra Hadjipavlou-Litina (Molecules, 2019)
Chalcones represent a class of small drug/druglike molecules with different and multitarget biological activities. Small multi-target drugs have attracted considerable interest in the last decade due their advantages in the treatment of complex and multifactorial diseases, since “one drug-one target” therapies have failed in many cases to demonstrate clinical efficacy. In this context, we designed and synthesized potential new small multi-target agents with lipoxygenase (LOX), acetyl cholinesterase (AChE) and lipid peroxidation inhibitory activities, as well as antioxidant activity based on 2-/4- hydroxy-chalcones and the bis-etherified bis-chalcone skeleton. Furthermore, the synthesized molecules were evaluated for their cytotoxicity. Simple chalcone b4 presents significant inhibitory activity against the 15-human LOX with an IC50 value 9.5 µM, interesting anti-AChE activity, and anti-lipid peroxidation behavior. Bis-etherified chalcone c12 is the most potent inhibitor of AChE within the bis-etherified bis-chalcones followed by c11. Bis-chalcones c11 and c12 were found to combine anti-LOX, anti-AchE, and anti-lipid peroxidation activities. It seems that the anti-lipid peroxidation activity supports the anti-LOX activity for the significantly active bis-chalcones. Our circular dichroism (CD) study identified two structures capable of interfering with the aggregation process of Aβ. Compounds c2 and c4 display additional protective actions against Alzheimer’s disease (AD) and add to the pleiotropic profile of the chalcone derivatives. Predicted results indicate that the majority of the compounds with the exception of c11 (144 Å) can cross the Blood Brain Barrier (BBB) and act in CNS. The results led us to propose new leads and to conclude that the presence of a double enone group supports better biological activities.